2022
DOI: 10.1111/jgh.15783
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk of hepatocellular carcinoma with tenofovir than entecavir treatment in subsets of chronic hepatitis B patients: an updated meta‐analysis

Abstract: Background and Aim Previous smaller meta‐analyses comparing the incidence of hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) patients treated with tenofovir disoproxil fumarate (TDF) versus entecavir (ETV) provided controversial results. This updated meta‐analysis aimed to reliably identify any difference in the HCC incidence between TDF‐treated or ETV‐treated CHB patients in general or in specific subgroups. Methods PubMed, EMBASE, Web of Science, and Cochrane Library were systematically searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
(369 reference statements)
1
16
0
Order By: Relevance
“…In addition to the trend of serum lipoprotein levels, the occurrence / recurrence of HCC between patients receiving TDF and ETV is controversial. Some studies found TDF to be associated with a lower risk of HCC occurrence than ETV in patients with chronic HBV infection, [3][4][5] but not others. 6 Similarly, one study found that both TDF and ETV showed similar recurrence-free and overall survival in patients with HBV-related HCC after hepatectomy, 7 but this was not found in another study.…”
Section: Letter: Entecavir Versus Tenofovir On Serum Lipoprotein Leve...mentioning
confidence: 98%
“…In addition to the trend of serum lipoprotein levels, the occurrence / recurrence of HCC between patients receiving TDF and ETV is controversial. Some studies found TDF to be associated with a lower risk of HCC occurrence than ETV in patients with chronic HBV infection, [3][4][5] but not others. 6 Similarly, one study found that both TDF and ETV showed similar recurrence-free and overall survival in patients with HBV-related HCC after hepatectomy, 7 but this was not found in another study.…”
Section: Letter: Entecavir Versus Tenofovir On Serum Lipoprotein Leve...mentioning
confidence: 98%
“… 60 A recent meta-analysis including 24 studies (37,771 CHB patients treated with TDF and 72,094 treated with ETV) has shown that TDF was associated with a lower HCC risk than ETV in Asian CHB patients (adjusted HR: 0.76, 95% CI: 0.66–0.87; 15 studies) or in NA-naïve patients (adjusted HR: 0.74, 95% CI: 0.65–0.84; 18 studies). 61 However, other studies have failed to demonstrate this association. 62 , 63 In Caucasian patients, the largest study including 1,935 patients from the PAGE-B cohort with a median follow-up of 7.5 years did not find differences on 5-year cumulative HCC incidence between ETV (5.4%) or TDF (6.0%).…”
Section: Nucleos(t)ide Analogues Efficacymentioning
confidence: 99%
“…In recent years, some studies have suggested that patients treated with TDF, compared to ETV, have a lower risk of developing HCC, especially in the Asian population, which has generated an intense debate with conflicting publications. [59][60][61][62][63][64] A large study including 29,350 patients from China showed a reduced HCC incidence in patients receiving TDF but only 1% of those with cirrhosis had received TDF. Moreover, important differences between groups regarding HCC risk factors were found; patients treated with TDF were younger, and more frequently HBeAg-positive, females, without cirrhosis, and without diabetes.…”
Section: Dovepressmentioning
confidence: 99%
“…109 However, several studies have been shown that patients with tenofovir disoproxil fumarate had lower incidence rate of HCC development than those with entecavir. 110,111 For example, a meta-analysis with 14 studies and 263,947 person-years follow-up revealed that patients with entecavir treatment had higher HCC risk than those with tenofovir disoproxil fumarate treatment (HR: 1.27, 95% CI:1.01-1.60, P=0.04). 110 Therefore, it remains controversial whether different antivirals may have distinct risk of HCC development.…”
Section: Hcc Incidence In Treated Patientsmentioning
confidence: 99%